Exploring Enamel Hypoplasia and Metabolic Impacts on Dental Structures in Chronic Kidney Disease: A Systematic Review and Meta-Analysis - Sadaf Ambreen; Amna Farrukh; Muhammad Mustafa; Ashar Hussain; Irum Naz; Fatima Ali (Pakistan Journal of Medicine and Dentistry, 2025)
Background: The loss of mineral homeostasis in patients with chronic kidney disease causes significant dental problems, including enamel hypoplasia and increased tooth damage. The current clinical treatments show an insufficient ability to resolve these metabolic dental complications. This review aimed to determine the prevalence, severity, and associated metabolic risk factors of enamel hypoplasia and tooth wear in patients with chronic kidney disease (CKD), and to evaluate the effectiveness of current interventions.